The Implementation of Wordwall as A Digital Learning Tool To Increase Student Learning Motivation in SMP Negeri 37 Medan - Napitupulu, Lilis Handayani; Salsabila; Tarigan, Egia Silvia (English Language Teaching Prima Journal (ELT), 2025)
This study looks at the use of Wordwall as a digital learning aid to increase student motivation in Class 7H at UPT SMP Negeri 37 Medan. Traditional teaching approaches frequently result in a lack of student involvement, which reduces motivation and learning results. Wordwall, an interactive educational platform, includes engaging activities including quizzes, word searches, and matching games that encourage students to actively engage in the learning process. To examine student perspectives and learning results, a qualitative study approach was used, which included observations, pre- and post-test evaluations, questionnaires, and documentation. The findings show a considerable increase in students' desire and knowledge, as evidenced by an increase in average score from 60.93% (pre-test) to 81.25% (post-test), a 33.34% improvement. Furthermore, questionnaire results indicated that the majority of students chose Wordwall over traditional ways of learning because it is more participatory and engaging. The study finds that Wordwall is a useful digital learning tool for increasing student motivation, engagement, and academic success. Educators should include Wordwall into their teaching practices to foster a more dynamic and collaborative learning environment. Future study might investigate Wordwall's long-term influence and compare its efficacy to other digital learning aids.